Enlightening the Cerebellopontine Angle: Intraoperative Indocyanine Green Angiography in Microvascular Decompression for Trigeminal Neuralgia - von Eckardstein, Kajetan L.; Mielke, Dorothee; Akhavan-Sigari, Reza; Rohde, Veit (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background and Study Aims In microvascular decompression of the trigeminal nerve for trigeminal neuralgia (TN), the site of conflict is occasionally difficult to identify. Endoscopy has been described to better evaluate the anatomical conflict in such situations. We hypothesized that indocyanine green (ICG) angiography could allow for better visualization of the compressing artery and its anatomical relation to the nerve.Material and Methods ICG angiography was performed in 17 TN patients undergoing microvascular decompression. We focused on whether ICG angiography is helpful in determining the site of conflict, particularly when not directly visible via the microscope, and whether fluorescence is strong enough to shine through the nerve obliterating the direct view of the compressing vessel.Results In four patients, the site of conflict was immediately apparent after opening the cerebellopontine cistern, and ICG angiography did not provide the neurosurgeon with additional information. In another two patients, imaging quality and fluorescence were too poor. Of the remaining 11 patients with a hidden site of nerve–vessel conflict, ICG angiography was found to be helpful in anticipating the site of compression and the course of the artery in 7 patients, particularly in regard to the so-called shining-through effect through fiber bundles of the thinned nerve. Of all the patients, 88% reported at least improvement or cessation of their symptoms, including all of the patients with a shine-through effect.Conclusion ICG angiography could be a helpful adjunct in decompressing the trigeminal nerve and can guide the surgeon to the nerve–vessel conflict. Intensity of the fluorescence is powerful enough to shine through thinned and splayed trigeminal nerve fiber bundles.
Keywords: indocyanine green angiography; microvascular decompression; trigeminal neuralgia